The Politics of China's Accession to the World Trade Organization - Feng, Hui (Routledge Contemporary China Series, 2006)
Grounded on a series of first-hand interviews with Chinese government officials, this book examines China's accession to the World Trade Organization, providing an 'inside' look at Chinese WTO accession negotiations. Presenting a systematic political economy model in analyzing Beijing's decision-making mechanisms, the book argues that China's WTO policy making is a state-led, leadership driven, and top-down process. Feng explores how China's determined political elite partly bypassed and partly restructured a largely reluctant and resistant bureaucracy, under constant pressure from an increasingly globalized international system. By addressing China's accession to the WTO from a political analysis perspective, the book provides a theoretically informed and intriguing examination of China's foreign economic policy making regime. The book highlights contemporary debates relating to state and institutionalist theory and provides new and useful insights into a significant development of this century.